Pengembangan Media Pembelajaran Komik pada Materi Peluang di Kelas VIII - Liana Septy; Yusuf Hartono; Ratu Ilma Indra Putri (Didaktik Matematika, 2015)
This study aim to knowing the characteristics of comics learning media in probability matter were valid, practical and have potential effects. This study showed that the characteristic of comics learning media in probability matter was valid that 1) according to the curriculum 2013; 2) according with the concept and definition of probability in class VIII; 3) the material in comic according with the level of students in class VIII; 4) using context that understood by students; 5) the material clustered, sequenced and easy to use; 6) has a simple design and communicative; 7) the color composition was not excessive; 8) commands and instructions in comics were easy to understand; and 9) the phrased according with EYD. The characteristic of comics learning media in probability matter was practical that 1) easy to use, understandable and easy to carry everywhere; 2) can help students understanding the material; and 3) attracting students to learn mathematics. The comics learning media have a potential effect to make the students motivated and improve the ability of students knowlegde seen from the observations and the results of a questionnaire to students. Based on observations obtained 90% of students showed an attitude of curiosity and 56,67% of students showed interest in the usefulness of mathematics. Based on the result of questionnaires, 100% of students expressed interest in learning to use comics learning media in probability matter. Based on students attitude assessment, 91,1% of students earn a good rating. From the skills assessment, 96,67% of students earn a good rating and for students knowledge assessment, 91,67% of students earn good rating.